2020
DOI: 10.1097/ta.0000000000002801
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline improves traumatic brain injury outcomes in a murine survival model

Abstract: BACKGROUND Traumatic brain injury (TBI) has significant morbidity and cost implications. Primary treatment modalities aim to decrease intracranial pressure; however, therapies targeting the underlying pathophysiology of a TBI are limited. The TBI-induced microvascular leak and secondary injury are largely due to proteolysis of the blood-brain barrier (BBB) by matrix metalloproteinase-9. We previously observed doxycycline's inhibitory affinity on matrix metalloproteinase-9 resulting in preserved BBB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Comprehensive reporting of neurological scores in TBI literature has been described, as there are many outcome measures that can be assessed by subjective priority, leading to evitable bias [ 57 , 58 ]. MEP revealed that 3D-CC-ST treatment could obviously address the questions of neurological dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive reporting of neurological scores in TBI literature has been described, as there are many outcome measures that can be assessed by subjective priority, leading to evitable bias [ 57 , 58 ]. MEP revealed that 3D-CC-ST treatment could obviously address the questions of neurological dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, available therapeutic options provide only symptomatic relief and unable to halt the progression of secondary injury that occur following TBI. 2 Recent preclinical studies 10 , 16 , 27 showed doxycycline as a promising choice that ameliorates the secondary brain injury. Hence, this study was designed to clinically investigate the benefit of adjunctive doxycycline use in acute TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Limited data are available regarding doxycycline use in TBI. One study showed improved neurological functions in mice treated with doxycycline following TBI; doxycycline preserved the BBB integrity by inhibiting the activity of the matrix metalloproteinase-9, 16 one of the main proteolytic enzymes implicated in BBB disruption. Recently, a randomized controlled trial assessed the effects of minocycline, a tetracycline derivative, on neurological outcomes in patients with brain trauma.…”
Section: Introductionmentioning
confidence: 99%